NetworK of Social Development Based on the Force of the Rrligion of PHRA Tep Sittajarn. (Noi Yannawuttho) - Ransri, Jesadakorn (Journal for Developing the Social and Community, 2022)
The present study was objected to survey the network for social development based on the power of faith of PHRA Tep Sittajarn (Noi Yannawuttho). The study was conducted by the use of interviewing and focus group discussion among six population groups: 1) the 4 current abbots of the temples that PHRA Tep Sittajarn used to stay 2) the 4 current leaders of the communities that PHRA Tep Sittajarn used to stay 3) the 4 people from Baan Nongbua, Wangsaeng subdistrict, Kaedam district, Mahasarakham Province 4) the 4 people from Wat Daowadung-Kaedam municipality community, Kaedam subdistrict, Kaedam district, Mahasarakham Province 5) the 4 people from Wat Patchimmatas community, Talard subdistrict, Muang district, Mahasarakham Province and 6) the 4 people from Wat Mahachai community, Talard subdistrict, Muang district, Mahasarakham Province. These were totaling 24 people. The data analysis is done by using Content analysis and presented in descriptive. The research results are as follows: 1) the PHRA Tep Sittajarn network groups comprise the group of clergies, civil servants, private organizations and people who respect the faith in PHRA Tep Sittajarn 2) the roles of each group of networks have different functions according to their own context 3) the methods for creating networks of PHRA Tep Sittajarn is establishing a network for social development using a form of request for clergy in both of superiors and subordinates cooperation as well as the related departments both public and private sectors without any coercion at all 4) in the coordination of the PHRA Tep Sittajarn network, what opportunities do you use to participate in government activities, state ceremony and the kin's invitation to meet a group of persons with various functions who will be able to support and facilitate the organization of public benefit activities in the name of the PHRA Tep Sittajarn? 5) in supervising the network of the PHRA Tep Sittajarn, it is a mutual care style with both informal (private groups and kin) and formal patterns (Subordinate priests is considered as officers and government officials) 6) the objective of the integration of the PHRA Tep Sittajarn network groups is in order to jointly inherit Buddhism as a Buddhist with the PHRA Tep Sittajarn network groups as the center of kin in Maha Sarakham Province and 7) the trust of the network towards Phra Thep Siddhartha is the result of his good behavior and the belief in his contributing on public society for Maha Sarakham Province.